Socio-economic Contributions of The Retail Sale of Mfumbwa (Gnetum africanum Welw.) Among Traders in the Uíge city, Angola - Mawunu, Monizi; Fernando, Agnaldo de Assunção Cardoso; Panzo, Abreu Zuanga; Mawunu, Nsimba Fineza Eduardo; Narciso, Hermenegildo Augusto; Lautenschläger, Thea; Koto-te-Nyiwa, Ngbolua; Ndiku, Luyindula; Luyeye, Lukoki (European Journal of Applied Sciences, 2021)
The trade of non-wood forest products in the town of Uíge, including the Mfumbwa (Gnetum africanum Welw.), is an important activity for the family economy and helps to meet the daily needs of households. The aim of this research was to find out the socio-economic contributions of the retail sale of Mfumbwa among households in the town of Uíge. The socio-economic surveys were based on a semi-structured questionnaire and submitted orally to the informants. The study was based on purposive sampling and took place between March and September of 2021 in the city of Uíge, northern Angola. A total of 56 informants were interviewed, all (100%) women. Mfumbwa retailing is a women’s business because the traders interviewed are exclusively (100%) women. The majority (38%) of retailers in Mfumbwa are between 18 and 30 years old. Trade is the main source (97%) of employment and income for the respondents. Mfumbwa retailers in the city of Uíge have an average of 15 years of experience in trading this product. The majority (63%) of retail traders in Mfumbwa have more than 30 years of experience in this activity. The average profit generated by the retail sale of Mfumbwa in the city of Uíge is 85.61 US per month/ retailer. The income from the retail sale of Mfumbwa is destined mainly to the strengthening of the household basket (25%), to the schooling of children (21%) and to the health of the household (18%). The retail sale of Mfumbwa in the city of Uíge improves the socio-economic conditions of the trading households, helps to combat unemployment and to supplement the family budget thanks to the income generated by this trade. Finally, to avoid the extinction of this species, it is imperative to develop sustainable conservation strategies.